Analisis Kondisi Kerusakan Jalan Penanganannya Pada Lapis Permukaan Perkerasan (Studi Kasus Jalan Kaliurang Km.13,5 – Km.15,5 Yogyakarta) - Agdicaller Vietrain Kaibi; Tjitra Handayani, Ani; Herna Puji Astutik (ReTII, 2023)
Pavement conditions affect the comfort, safety and safety of road users. However, there are several points on the Kaliurang road section, especially at KM.13.5 – KM.15.5, which have started to experience minor damage, if maintenance activities are not carried out, the road will experience increasingly severe damage. In this study an analysis of road damage will be carried out using the Pavement Condition Index (PCI) method which aims to determine the type of damage, the severity of the damage, and the amount of damage. After analyzing the damage that has occurred, an alternative treatment will be determined using the standard method of the Director General of Highways 1995. Based on the results of the study, it was found that the types of damage to the Jalan Kaliurang section KM.13.5 – KM. 15.5, Yogyakarta, among others, crocodile skin cracks, checkered cracks, holes, fillings, road side cracks, aggregate wear and grain release with an average damage in all segments of 82.1%. Based on the existing classification, 85-100 namely excellent, 70-84 very good, 55-69 good, 40-54 fair, 25-39 poor, 10-24 very poor and 0-9 failed. The quality of Jalan Kaliurang KM.13.5 – KM.15.5, Yogyakarta is at a very good level with alternative treatments being carried out, namely P2 (local asphalt coating) and P3 (covering cracks).